Hubungan Sikap dengan Kepercayaaan Diri Remaja Mengatasi Kekerasan Verbal di SMP Negeri 16 Palangka Raya - Meilitha Carolina; Nia Pristina; Anita Gresela (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Adolescents are a group at risk of emotional and social changes, including the impact of verbal abuse that can lower self-confidence. At SMP Negeri 16 Palangka Raya, some students often face taunts, insults, and hurtful labels from their peers. Some students exhibit shy behavior, withdraw, and have low self-confidence. Verbal abuse is often seen as a joke, but it can negatively affect the psychological condition of adolescents. Positive attitudes are believed to help adolescents face verbal abuse more constructively. This study aims to analyze the relationship between attitudes and adolescents' self-confidence in dealing with verbal abuse. The study used a quantitative method with a correlational design and a cross-sectional approach. A total of 55 students from classes VIII-1 and VIII-2 were selected as samples using total sampling technique. Data were collected using questionnaires and analyzed using Spearman Rank test. The results showed that all respondents had a positive attitude, but 81.8% had only moderate self-confidence. The p-value of 0.007 (< 0.05) indicates a significant relationship between attitude and self-confidence. This suggests that positive attitude alone is not enough, and emotional education and psychosocial support are needed to improve adolescents' self-confidence in dealing with verbal abuse.